Comparison of Healing Outcomes Between K-Wire Pin and Screw Fixation in Lateral Humerus Condyle Fractures in Pediatric Population: A Systematic Review and Meta-Analysis - Tommy Mandagi; Iman Dwi Winanto; Reza Mahruzza (Universitas Muhammadiyah Palu, 2025)
Lateral condylar humerus fractures are common pediatric elbow injuries, often resulting from trauma or falls. These fractures are typically seen in children aged 6 to 10 years and require appropriate fixation to prevent complications like malunion and nonunion. This systematic review and meta-analysis compare the outcomes of K-wire pin and screw fixation methods for pediatric lateral condylar humerus fractures. Data from studies published in the last decade were analyzed, focusing on clinical outcomes such as healing time, complications (delayed union, non-union, infection, stiffness), and functional recovery. Results show no significant difference in delayed union or non-union between the two methods. However, screw fixation was associated with a higher risk of non-union and avascular necrosis, although these differences were not statistically significant. In contrast, K-wire pin fixation was linked to a significantly higher risk of infection (RR 6.53) and stiffness (RR 1.77) compared to screw fixation. No significant difference was found in lateral overgrowth, fishtail deformity, or cubitus varus. These findings suggest that while screw fixation offers greater stability, K-wire pin fixation may be more prone to complications. Clinicians should carefully consider fracture type and patient-specific factors when choosing the fixation method.